Working conditions and mental health of employees suffering from common mental disorders in Germany with special consideration to the migration generation - Regina Herold; Yesim Erim; Ute B. Schröder; Meike Heming; Eva Rothermund-Nassir; Jeannette Weber; Nicole Rosalinde Hander; Eva Morawa (BMC Psychology, 2026)
Abstract Purpose This study examines working conditions, mental health and their association among mentally burdened employees in Germany attending psychotherapeutic consultation at work, considering first- and second-generation migrants. Methods Baseline data from a randomized controlled trial on psychotherapeutic consultation at work (friaa study) were analyzed. Using χ²- and two-sided t -tests and one-way ANOVAs, differences between individuals with and without migration background (MB) as well as individuals without MB and first- and second-generation migrants were assessed regarding working conditions (self-constructed questions, five scales of the COPSOQ, PSC) and depressive (PHQ-9), anxiety (GAD-2) and somatic symptoms (SSS-8). Associations between working conditions and mental health were calculated for the entire sample and separately for individuals with and without MB using linear regression analyses. Results Among 549 participants (54.8% female, mean age: 45.9 years ( SD = 11.0), 12.4% had a MB. Individuals with MB more often worked in jobs associated with lower socio-economic status (blue-collar work: p =.008, fewer subordinates: p